Desenvolvimento de Scaptotrigona postica Latreille, 1807 exposta a concentrações subletais de agrotóxicos com foco nos órgãos sensoriais - Bovo, Joyce (2023)
Bees are primary pollinators of native plants and economically important crops. With the indiscriminate use of pesticides in Brazil, studies related to the effects of these products on these species are necessary. Nowadays, risk assessment tests use an exotic species, but there are knowledge gaps regarding its use to represent native species, such as stingless bees. To contribute to the knowledge about these species, this work aimed to evaluate if the exposure to sublethal concentrations of the insecticide thiamethoxam and the fungicide pyraclostrobin, both individually and mixed, affects the post-embryonic development and structures development of the olfactory and visual systems of the species Scaptotrigona postica Latreille, 1807 (Hymenoptera, Apidae). For this purpose, we exposed larvae to the following treatments: CTL (Negative control), ACE (Solvent control - acetone), DIM (Positive control - dimethoate), TMX (Thiamethoxam), PYR (Pyraclostrobin), and TMX+PYR (Mixture). The concentrations used were 0.044 ng a.i./larva of thiamethoxam and 69.675 ng a.i./larva of pyraclostrobin. We evaluated post-embryonic development through mortality rates, pupation, larval emergence, and pupal emergence rates. In addition, we evaluated the antennae and eyes through morphological and morphometric analyses using scanning electron microscopy (SEM). We identified and quantified the types of sensilla present on the antennae, and measured the ocular facets diagonal. The results indicated that thiamethoxam advanced the pupal stage of white-eyed individuals. The mixture of thiamethoxam and pyraclostrobin interfered with pupal emergence and caused delays in the pink-eyed and brown-eyed pupal stages. In the groups exposed to pyraclostrobin and the mixture of the pesticides, we observed a delay of emergence. About sensory structures, thiamethoxam interfered with the coeloconic and ampullaceous sensilla development, but the same did not happen for pyraclostrobin and the mixed groups. No changes were observed in the exposed groups for the other types of sensilla and ocular facets. Our study concluded that exposure to sublethal concentrations of thiamethoxam and pyraclostrobin, individually and mixed, affected the pupal development times and emergence of S. postica. However, only thiamethoxam interfered with the development of sensilla.